MoP is a novel, noble-metal-free cocatalyst for enhanced photocatalytic hydrogen production from water under visible light1. Issue 33 (7th September 2015) - Yue, Qiudi; Wan, Yangyang; Sun, Zijun; Wu, Xiaojun; Yuan, Yupeng; Du, Pingwu
<x xml:space="preserve">Abstract</x> The present study shows that MoP is a stable and highly active cocatalyst to promote photocatalytic H2 production from water when attached on the semiconductor surface.